2015
DOI: 10.1364/oe.23.030237
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Faradaic electrochemical impedance spectroscopy into a scalable surface plasmon biosensor for in tandem detection

Abstract: We present an integrated label-free biosensor based on surface plasmon resonance (SPR) and Faradaic electrochemical impedance spectroscopy (f-EIS) sensing modalities, for the simultaneous detection of biological analytes. Analyte detection is based on the angular spectroscopy of surface plasmon resonance and the extraction of charge transfer resistance values from reduction-oxidation reactions at the gold surface, as responses to functionalized surface binding events. To collocate the measurement areas and ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…To fabricate the plasmonic IR sensing device illustrated in the inset of Figure b, an AZ1505 photoresist layer is spun onto a silicon substrate to a 400 nm thickness, UV holographically exposed, and developed into quasi-sinusoidal grating with 570 nm periodicity, followed by sputtering of 5 nm of adhesion titanium and 75 nm of gold (Denton Discovery 18). The fabrication procedure for the metallized gratings employs similar methods and instrumentation as previously reported. , An IR absorbing layer is developed by sputtering 200 nm of silicon nitride (Si 3 N 4 ) onto the SPP grating layers; IR absorption in the thermal 8–14 μm spectral band is verified by Fourier transform infrared (FTIR) spectroscopic measurement in attenuated total internal reflection (ATR) (ThermoFisher Nicolet). By ellipsometric measurement, the refractive index of the silicon nitride layer was measured to be approximately 1.91 for 632.8 nm wavelength light.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To fabricate the plasmonic IR sensing device illustrated in the inset of Figure b, an AZ1505 photoresist layer is spun onto a silicon substrate to a 400 nm thickness, UV holographically exposed, and developed into quasi-sinusoidal grating with 570 nm periodicity, followed by sputtering of 5 nm of adhesion titanium and 75 nm of gold (Denton Discovery 18). The fabrication procedure for the metallized gratings employs similar methods and instrumentation as previously reported. , An IR absorbing layer is developed by sputtering 200 nm of silicon nitride (Si 3 N 4 ) onto the SPP grating layers; IR absorption in the thermal 8–14 μm spectral band is verified by Fourier transform infrared (FTIR) spectroscopic measurement in attenuated total internal reflection (ATR) (ThermoFisher Nicolet). By ellipsometric measurement, the refractive index of the silicon nitride layer was measured to be approximately 1.91 for 632.8 nm wavelength light.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, the majority of the literature describes AC sensing based on single-phase lock-in detection, where only the magnitude of the impedance, or power response of the NW (or carbon nanotube), is investigated [ 24 , 25 , 26 ]. Only a few recent manuscripts describe NW complex AC sensing, measuring the analyte with both magnitude and phase of the impedance [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several devices for sensing applications have been reported. Hong et al [5] demonstrated the benefits of combining surface plasmon resonance (SPR) together with Faradaic electromechanical impedance spectroscopy for the purpose of simultaneous detection of biological analytes. With this approach, they demonstrated biotinylated surface capture of neutravidin concentrations as low as 10 nM with a 5.5 nM limit of detection.…”
Section: Introduction To the Focus Issue On Surface Plasmon Photonicsmentioning
confidence: 99%